Convergent Richtmyer–Meshkov instability of light gas layer with perturbed outer surface. (17th December 2019) - Li, Jianming; Ding, Juchun; Si, Ting; Luo, Xisheng
Abstract : Abstract : The Richtmyer–Meshkov instability of a helium layer surrounded by air is studied in a semi-annular convergent shock tube by high-speed schlieren photography. The gas layer is generated by an improved soap film technique such that its boundary shapes and thickness are precisely controlled. It is observed that the inner interface of the shocked light gas layer remains nearly undisturbed during the experimental time, even after the reshock, which is distinct from its counterpart in the heavy gas layer. This can be ascribed to the faster decay of the perturbation amplitude of the transmitted shock in the helium layer and Rayleigh–Taylor stabilization on the inner surface (light/heavy) during flow deceleration. The outer interface first experiences 'accelerated' phase inversion owing to geometric convergence, and later suffers a continuous deformation. Compared with a sole heavy/light interface, the wave influence (interface coupling) inhibits (promotes) growth of instability of the outer interface.